PRICE REACTION TO RIGHTS ISSUES ANNOUNCEMENT: NEW EVIDENCE FROM INDONESIA - Suthiono, Henry; Atmaja, Lukas Setia (Jurnal Aplikasi Manajemen, 2019)
Research on rights issues has been carried out in Indonesia with mixed results and in a short period, between 3-8 years. The results of research on rights issues in Indonesia are mostly insignificant. The number of sleep stocks can cause that. Therefore, a longer period of research is needed to examine the reaction of stock prices to the announcement of rights issues. This study uses data that has been available from 1991 to 2016 and uses an event study methodology that considers thin trading. This study found significant negative abnormal returns between -1.66% and -2.80% at different periods. Therefore, this study does not support that the Indonesia Stock Exchange is in a semi-strong efficiency. The characteristic of companies in Indonesia is the family company, but this is not considered in this study, which can be considered for further research.